Commentary on the skills of an effective administrator - Cariño, Isidro (Philippine Engineering Journal)
Twenty years ago, Robert L. Katz pointed out that management's real concern should be for what a person can do rather than what he is. And he identifies three basic skills- technical, human and conceptual-which every successful manager must have in varying degrees, according to the level of management at which he is operating. Today, he stands by his original statement, but he refines a number of ideas in the light of his subsequent experience.